Psychopharmacological Treatment for Posttraumatic Stress Disorders in Naval Military Subjects (2018)
Introduction: Posttraumatic Stress Disorder (PTSD) is a psychiatric syndrome known since 1980 with multiple names in the military field. Its etiology is multicausal, whose predominant factor is the lack of adaptation and managing with events considered traumatic. Objective. To describe the clinical characteristics such as the type of psychological and pharmacological treatment received by the naval military with diagnosis of Posttraumatic Stress Disorder at the Psychiatric Unit of Cartagena’s Naval Hospital. Methodology: A descriptive, retrospective cross-sectional study with an associative approach (Crosstabulation). The sample was 242 navy subjects with PTSD diagnosis. The information was collected with a data collection form of medical records. The information analysis was developed through the program SPSS ® 21.0. Chi2 and value of p≤0.05 calculation was applied through the crossing of variables. Results: The most prevalent type of traumatic event was the one represented by combat with the presence of depressive disorders and anxiety with a value of p≤0.05. Conclusions: The PTSD severity is related to the severity of the event, in addition if the trumatic event was repetitive.